2018
DOI: 10.3762/bjoc.14.245
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of 1,2-disubstituted 4-quinolone analogues of Pseudonocardia sp. natural products

Abstract: A series of analogues of Pseudonocardia sp. natural products were synthesized, which have been reported to possess potent antibacterial activity against Helicobacter pylori and induce growth defects in Escherichia coli and Staphylococcus aureus. Taking inspiration from a methodology used in our total synthesis of natural products, we applied this methodology to access analogues possessing bulky N-substituents, traditionally considered to be challenging scaffolds. Screening of the library provided valuable insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…The actinomycete Pseudonocardia sp. CL38489 can produce a family of quinolones and is active against Helicobacter pylori , which is responsible for the generation of numerous digestive disorders [26–28]. In addition, it has been reported that Pseudonocardia can convert vitamin D 3 to calcifediol and calcitriol by using resting cells [29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…The actinomycete Pseudonocardia sp. CL38489 can produce a family of quinolones and is active against Helicobacter pylori , which is responsible for the generation of numerous digestive disorders [26–28]. In addition, it has been reported that Pseudonocardia can convert vitamin D 3 to calcifediol and calcitriol by using resting cells [29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in position 2 were, recently, also explored because PQS (Pseudomonas quinolone signal) and HHQ (2-heptyl-4(1H)-quinolone), compounds responsible for the quorum sensing (QS) of Pseudomonas aeruginosa (Figure 12), these molecules regulate the expression of genes that code virulence factors in this bacteria (GEDDIS et al, 2018;Li & Clark, 2020;RAMOS et al, 2020). So, Geddis et al (2018) reported synthetic compounds, we will focus on the compounds 21a, 21b and 21c (Figure 14), and tested the growth of Staphylococcus aureus 25923 in the presence of 200 μM of each compound using gentamicin as positive control. They observed a strong effect comparable to the standard when the optical density 600 (OD600) was measured.…”
Section: Developmentmentioning
confidence: 99%
“…These naturally occurring quinolones present a geranyl or oxidized geranyl side chain at position C-2 compared to fatty acid-derived alkyl or alkenyl chains usually found in microbial quinolones. Although these compounds have been described over twenty years ago, no therapy has been developed based on these quinolones; however, some advances have been made in the synthesis of those structures [ 62 ]. We will be watchful for the development of new therapies based on the structures of naturally occurring quinolones.…”
Section: Synthetic and Natural-occurring Quinolonesmentioning
confidence: 99%